Emotional wellbeing in neurodivergent populations - Pincus, J. David; Beller, Ken (Frontiers in Psychology, 2025)
IntroductionUnderstanding emotional wellbeing in neurodivergent populations remains a critical yet underexplored area in psychological research.MethodsThis study employs AgileBrain, a novel assessment rooted in a neuroscience-informed model of human motivation, to evaluate emotional activation, valence, and unmet emotional needs across a large and diverse sample of adults reporting diagnosed neurodivergent conditions. The sample includes individuals self-identifying with ADHD, ASD, DCD, SID, SH, OCD, and other conditions, alongside a neurotypical comparison group.ResultsFindings reveal systematic variations in emotional wellbeing indexed by three key indicators: (1) overall valence (positive vs. negative emotional needs), (2) activation level (intensity of emotional needs), and (3) the resulting wellbeing index (a composite of the first two). Neurotypical respondents exhibited the highest wellbeing, characterized by low activation and positive valence. DCD and ASD groups showed moderate wellbeing with elevated activation, while groups identifying with SID, SH, and OCD exhibited increasingly negative need valence and a steep drop in overall wellbeing. Notably, the largest group—those reporting ADHD—showed moderate activation with a negative need profile, resulting in low overall wellbeing. A final group categorized as “other conditions” (e.g., depression, anxiety, bipolar disorder, PTSD) exhibited the most extreme negativity in need valence and the lowest wellbeing scores.DiscussionThe study demonstrates the value of a needs-based framework for understanding emotional profiles in neurodivergent populations. By going beyond diagnostic labels to quantify emotional need dynamics, this approach offers scalable, quantitative insights into the lived experience of neurodivergent individuals and highlights distinct pathways to improving wellbeing. The results support the potential for targeted interventions grounded in emotional need fulfillment to enhance resilience and support across diverse neurodivergent profiles.